Threat perception of the rural-urban migration as a linkage to the rise of crime: Bangladesh perspective - Khanam, Taslima (IIUC Studies, 2018)
At present the rise of urban crime falls within the gripping focus of criminal justice and criminology. Researchers endeavor to figure out urban schemes of crime which linked with rural-urban migration. Although, rural-urban migration mostly concerns the subject of sociology, this article viewed from jurisprudential perspectives under the sociological school to study social doctrines in relation with the migration as social phenomena and to criticize as to their relation to social condition and social progress. This observable fact of rural-urban migration could also be apprehended as a supply of the intensifying and distressing crisis in urban areas which is rising violent behavior and criminal activities. This article uncovers the cause and effect of increasing crime under interrelation between migration and the security précised by the law and order environment. The author finds the needs and changes of the society due to the migration of a huge mass of people from rural to urban areas in Bangladesh. Finally, the paper recommends the balance of conflicting interests from social, political and ethical stance to facilitating the policies and laws concerned. IIUC Studies Vol.13 December 2016: 69-82